The Effect of Public Exercise on Increasing Breast Milk Production in Post Partum Mothers in Puskesmas Tanjung Tiram - Basyariah Lubis (Universitas Aisyah Pringsewu, 2021)
In Indonesia, there are many postpartum mothers who cannot exclusively breastfeed for 6 months due to decreasing milk production, causing mothers to give formula milk. Meanwhile, efforts to increase breast milk production can be obtained apart from using green vegetables, but also through Postpartum Gymnastics. This research is a quasi-experimental research method with the design used in this study using One group pre-test and post-test. The study was conducted at the Tanjung Tiram Health Center, Batu Bara Regency 2021. The study population was 30 people, with a sample of 15 respondents. The sampling technique used was non-probability sampling with incidental sampling. Data analysis used univariate analysis, bivariate analysis with Paired Sample t-test to determine differences in breast milk production before and after postpartum exercise. Based on the results of data analysis, t count = 18.52, with df = 14 and (5%) obtained t table = 2.042. It turns out that t count more than t table (18.52 more than 2.042), meaning that Ho is rejected, and Ha is accepted. This means that there is an increase in breast milk production after postpartum exercise for postpartum mothers at the Tanjung Tiram Health Center, Batu Bara Regency 2021. It is recommended that health workers are expected to provide health education to postpartum mothers about the benefits and proper techniques of postpartum exercise so as to increase the coverage of exclusive breastfeeding.Abstrak: Di Indonesia terdapat banyak ibu nifas yang tidak dapat menyusui secara eksklusif selama 6 bulan dikarenakan produksi ASI yang semakin menurun sehingga menyebabkan ibu memberikan susu formula. Sedangkan upaya untuk memperbanyak produksi ASI selain diperoleh dengan memanfaatkan sayur sayuran hijau juga dapat melalui Senam Nifas. Penelitian ini adalah penelitian metode Quasi Eksperimental dengan desain yang digunakan dalam penelitian ini yaitu dengan menggunakan One group pretest and post test. Penelitian dilakukan di Puskesmas Tanjung Tiram Kabupaten Batu Bara 2021. Populasi penelitian sebanyak 30 orang, dengan jumlah sampel 15 responden. Teknik pengambilan besar sampel menggunakan teknik nonprobability sampling dengan acidental sampling. Analisis data menggunakan analisis univariat, analisis bivariat dengan Paired Sample t-test untuk mengetahui perbedaan produksi ASI sebelum dan sesudah diberikan senam nifas. Berdasarkan hasil analisa data didapatkan t hitung = 18.52, dengan df =14 dan ? (5%) didapatkan t table = 2.042. Ternyata t hitung lebih dari t table (18.52 lebih dari 2.042), berarti Ho di tolak dan Ha diterima. Artinya terdapat peningkatan produksi ASI setelah dilakukan senam nifas pada ibu post partum di Puskesmas Tanjung Tiram Kabupaten Batu Bara 2021. Disarankan petugas kesehatan diharapkan memberikan pendidikan kesehatan kepada ibu nifas tentang manfaat dan teknik Senam Nifas yang tepat sehingga meningkatkan cakupan ASI Eksklusif.